Individualized Homoeopathic Prescription of Sulphur in Acute Cystitis: A Case Report - Dr. Janakiben Bhanvadia; Dr. Kirtida Desai (The Bioscan, 2025)
Urinary tract related complaints are a very common illness encountered in clinical practice nowadays. After respiratory and gastrointestinal infections UTI remains the third most common infection experienced by individuals. Acute cystitis is a common urinary tract infection characterized by dysuria, frequency, urgency and suprapubic discomfort. Females are more prone to catch infection because of short urethra and close proximity to anus. Approximately 1 in 3 women will have had at least 1 episode of UTI requiring antimicrobial therapy by age of 24 years. Homoeopathy is preferable over antibiotics to avoid drug resistance, adverse effects and recurrent infections, while addressing the patient constitutionally. This case report describes the successful management of acute cystitis in a female patient using the individualized homoeopathic remedy Sulphur. Marked improvement was observed within a short period with complete resolution of symptoms and no recurrence on follow ups. This case highlights homoeopathy as safe, effective and holistic alternative in acute cystitis management. KEYWORDS Cystitis, Homoeopathy, Sulphur, Acute Cystitis symptom score (ACSS)